Seagrasses: Biology, Ecology and Conservation - Larkum, Anthony W. D.; Orth, Robert J.; Duarte, Carlos (Springer Netherlands : Imprint: Springer, 2006)
Seagrasses are unique plants; the only group of flowering plants to recolonise the sea. They occur on every continental margin, except Antarctica, and form ecosystems which have important roles in fisheries, fish nursery grounds, prawn fisheries, habitat diversity and sediment stabilisation. Over the last two decades there has been an explosion of research and information on all aspects of seagrass biology. However the compilation of all this work into one book has not been attempted previously. In this book experts in 26 areas of seagrass biology present their work in chapters which are state-of-the-art and designed to be useful to students and researchers alike. The book not only focuses on what has been discovered but what exciting areas are left to discover. The book is divided into sections on taxonomy, anatomy, reproduction, ecology, physiology, fisheries, management, conservation and landscape ecology. It is destined to become the chosen text on seagrasses for any marine biology course. About the Editors: Anthony Larkum is Emeritus Professor and Deputy Director of the Centre for Biological Informatics and Technology at the University of Sudney, Australia. Over the past 45 years his research has centred on photosynthesis and marine biology, especially of algae and seagrasses. He is the author of six books, including "SeagrassBiology: An Australasian Perspective" (Elsevier, 1989) and "Photosynthesis of Algae" (Kluwer, 2003) and has published over 170 research papers. He is the recipient of many international awards and is on the editorial board of Trends in Plant Science. Robert J. Orth is a Professor of Marine Science in the School of Marine Science and the Virginia Institute of Marine Science at the College of William Mary, Gloucester Pt., Virginia. His research over the past 35 years has addressed aspects of faunal interactions within seagrass meadows, seed ecology, restoration, and factors influencing the distribution and abundance of meadows in Chesapeake Bay. His work has been closely tied to seagrass management in this region. He has published more than 100 research papers, and co-authored several special issues of scientific journals dealing with seagrasses and one book (Changes in Fluxes in Estuaries). He is past president of the Estuarine Research Federation. Carlos M. Duarte is a research professor with the Spanish Council for Scientific Research at IMEDEA (Esporles, Majorca, Spain). His research addresses all aspects of seagrass biology and ecology, emphasising seagrass demography, colonisation and recovery processes and their role in the ecosystem. He has authored more than 250 papers in international journals and an introductory book on Seagrass Ecology, is co-editor in chief of the journal "Estuaries and Coasts" and has received several international awards.